Investigation of whey protein concentration by ultrafiltration elements designed for water treatment - Kukučka Miroslav Đ.; Kukučka Nikoleta M. (Hemijska Industrija, 2013)
Suitability of polysulfone ultrafiltration membranes (UFM) commercial designed for water treatment have been investigated for separation of protein (PR) from sweet whey. Ultrafiltration (UF) of whey originated from dairy has been realized by self-made pilot plant which has been in service about one year. Influence of two whey temperatures (9 oC and 30 oC) on efficiency of protein concentration has been examined. Application of investigated UF elements has given whey protein concentrate (WPC) with 5 to 6 times excess amount of protein content in regard to starting one. In the same time the prevalent content of lactose has been removed to permeate. Better results have been occurred during the cold whey filtration. Besides the fact that molecular weight cut-off (MWCO) of investigated membranes were 50-100 kDa, results showed very successful concentrating of whey proteins of dominantly lower molar weights than 50-100 kDa. Investigated membranes are beneficial for design and construction of UF plants for exploitation in small dairies.